Scribo Ergo Cogito: Reflexivity through Writing - Kaufman, Peter (TRAILS: Teaching Resources and Innovations Library for Sociology, 2013)
This article builds on the concept of "writing as thinking" by describing an in-class, cumulative, peer-writing exercise that helps foster reflexivity. Reflexivity is understood as a process of seeing and a process of being. To be reflexive means that we are fully conscious of the lenses through which we view the world. It suggests that we understand both our situationality and our positionality. In this sense, reflexivity is an essential component of the sociological imagination. Three themes of reflexivity commonly arise from this exercise: developing reflexivity, reinforcing reflexivity, and resisting reflexivity. These themes are discussed and illustrated with full-length excerpts of students’ work.